The prospect of using technical means to develop special speed-strength and coordination abilities of students in sword fencing - Britsky, Vadim A.; Aikin, Vladimir A.; Mikhalev, Vladimir I. (Физическое воспитание и студенческий спорт)
Increasing the effectiveness of training process among students in sword fencing at different stages of longterm= training will largely be determined by the speed, strength and coordination abilities of those involved, first of all, with special physical fitness and specialized manifestations of elements of fencing technique. It was assumed that the use of an additional tool (simulator) in the training process for both young athletes and students of sword-fencers will increase the level of special speed-strength and coordination abilities and improve their technical readiness. To do this, a pedagogical experiment was carried out aimed at checking effectiveness of the simulator and diagnostic device “Fencing target, electronic-mechanical” among sword-fencers in the competitive period. Significant increases in fixed parameters were obtained in the experimental group (from 14.1–41.4%), while in the control group significant increases reached 15.8%.